The analysis of arabica coffee quality in matano coffee using the six sigma DMAIC method - Utami, Silvia Firda; Muhamad Faiz Almatsir; Ismi Mashabai; Nurul Hudaningsih (JENIUS : Jurnal Terapan Teknik Industri, 2023)
Sumbawa Regency is the largest coffee-producing area in West Nusa Tenggara, which has an area of ​​4,561.32 hectares with a total production of 2,514 tons per year. Matano Coffee is one of the UMKM that wants to improve the quality of its products so that it can continue to compete in the local and national markets. This research aims to improve the quality of UMKM Matano Coffee products, especially Sumbawa arabica coffee, as well as to get the best effort to reduce defects in Sumbawa arabica coffee. This research uses the Six Sigma Define, Measure, Analyze, Improvement, Control (DMAIC) method. The results of this study show that there are 4 factors that cause defects in Arabica coffee products: production tools, raw materials, people, and management. The most influencing factor is the raw material factor, where the defective coffee beans will affect the quality of Arabica coffee products, from the physical appearance to the dominant bitter taste. Efforts to improve the quality of Matano Coffee to minimize the occurrence of defects in Arabica coffee include carrying out short-term solutions, namely monitoring during the roasting or sangria process, as well as monitoring the temperature of the fire and the temperature of the drum machine by the owner of Matano Coffee.